Crystal and molecular structure of cis-Dichlorobis(triphenyl-phosphite) Platinum(II) - Sabounchei, Seyyed Javad (Molecules, 2001)
The single crystal structure of cis-dichlorobis(triphenyphosphite) platinum(II), [PtCl(2)(P(OPh)(3))(2)] has been determined. This complex crystallises in the orthorhombic space group, P2(1)2(1)2(1) with cell constant, a=10.4135(13), b=14.0635(16), c=23.505(3) Ǻ and v=3448.3(7) Ǻ (3). The Pt-Cl(1) and Pt-Cl(2) distances are 2.3390(10) Ǻ and 2.3256 Ǻ, which are longer than Pt-P(1) and Pt-P(2) with 2.1985(12) Ǻ and 2.1998(10) Ǻ respectively. These data together with bond angles suggest a distorted square planar geometry for this complex with two chlorine ligands in a cis configuration.